Ireland : Selected Issues. (IMF Staff Country Reports; Country Report, 2015)
This Selected Issues paper outlines some of the technical issues associated with implementation of European Union (EU) fiscal rules in Ireland. Ireland is expected to exit the Excessive Deficit Procedure in 2015. From a peak of 13.3 percent of GDP in 2010, the overall deficit was brought down to an estimated 3.9 percent of GDP in 2014. In this paper, EU fiscal rule framework is discussed in more detail. Technical challenges in estimating potential output in Ireland, and some options to address these challenges are also outlined.